Aggressive Periodontitis: A case report with exome sequencing and functional characterization of identified variant - Waheed Awotoye; Patricia Ayanbadejo; Steven Eliason; Kehinde Umeizudike; Ayodele Ogundana; Dan Su; Tadkamol Krongbaramee; Emmanuel Aladenika; Azeez Alade; Abimbola Oladayo; Abdul-Warith Akinshipo; Tamara Busch; et al. (Nigerian Dental Journal)
Aggressive periodontitis (AgP) is characterized by rapid and progressive destruction of the periodontal tissues and eventual tooth loss. Genetic risk contributions have been explored and rare mutations in NOD2 were reported. Sequencing analysis of the coding regions of NOD2 was conducted using individuals of African ancestry, to identify the pathogenic protein-altering variants in individuals with AgP using: 1) In Silico tools and clinical variant classification system; 2) IF staining to understand the expression pattern, and 3) In vitro cell based assay to understand the variant protein function. We discovered a novel nonsense NOD2 variant (c.835G>T; p.Glu279Ter) ; a truncating protein variant that is clinically pathogenic, and the gene-product lacks domains regulating inflammatory responses. Murine studies suggest that this gene contributes to tooth development. In vitro analysis suggests a dominant-negative effect of the variant. NOD2 gene is expressed in the immune cells and periodontal tissues and regulates the inflammatory response within this tissue. This truncating variant found in one African family, which results in a dominant-negative effect, could explain the exacerbated immune response to pathogens in the pathogenesis of this periodontal disease.